2021
DOI: 10.4028/www.scientific.net/jera.54.118
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Viscous Dissipation and Thermal Radiation in Siskoferronanofluid Flow over a Porous Medium

Abstract: This Paper contributes heat transfer phenomena in mixed convection flow of Siskoferronanofluidover a porous surface in the presence of a temperature gradient heat sink with prescribed heatflux. The effect of viscous dissipation and thermal radiation on the flow field is also taken in to consideration. The three types of ferromagnetic particles Nickel Zinc ferrite (Ni–ZnFe2O4), ManganeseZinc ferrite (Mn1/2Zn1/2Fe2O4) and Cobalt ferrite (CoFe2O4) are considered with water (H2O)and Ethylene Glycol (C2H6O2) as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Here, the Sisko Ferro nanofluid's governing flow equations are written in the system of Cartesian coordinates. For the isotropic incompressible flow of a Sisko fluid, the rheological equation of state is given by 22 . …”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…Here, the Sisko Ferro nanofluid's governing flow equations are written in the system of Cartesian coordinates. For the isotropic incompressible flow of a Sisko fluid, the rheological equation of state is given by 22 . …”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…Sajid et al 32 identified effects on a non-Newtonian fluid flowing on a stretchy surface under the influence of heat radiation, including variable thermal conductivity and molecular diffusivity. Narendra et al 33 and Saritha et al 34 studied radiation impact on MHD flow. Famakinwa et al 35 studied thermal radiation with viscous dissipation containing hybrid nanoelements of two oriented sides.…”
mentioning
confidence: 99%